Effect of digital detox program on electronic screen syndrome among preparatory school students - Sayeda Mohamed Mohamed; Lamiaa Saad Abdallah; Fatma Nagy Kotb Ali (Wiley, 2023)
Abstract Aim The aim of this study was to determine the digital detox programme's impact on the electronic screen syndrome among preparatory school students. Design A quasi‐experimental pre‐ and posttest group was used. Methods Two preparatory governmental schools. Sample: purposive sample consists of 105 students. Tools: Two tools used for data collection: Student's datasheet and Electronic Screen Addiction Scale. The data collection period took six months, from September 2021 to February 2022. Results The high rate of screen addiction among students dropped to 14.3% in the posttest compared with 20.0% in the pre‐test. Moreover, the students' proportion with moderate screen addiction dropped from 65.7% on the pre‐test to 43.8% on the posttest. Furthermore, screen addiction students with lower levels were about 41.9% in the posttest and 14.3% in the pre‐test. Conclusions There was a highly statistically significant difference between school students' total electronic screen scores in the pre‐ and posttest. A preventive care programme is recommended for high school children and helps raise screen addiction's awareness and its negative consequences. Patient or Public Contribution No patient or public contribution.